Vision affects tactile target and distractor processing even when space is task-irrelevant - Wesslein, Ann-Katrin; Spence, Charles; Frings, Christian (Frontiers in Psychology, 2014)
The human brain is adapted to integrate the information from multiple sensory modalities into coherent, robust representations of the objects and events in the external world. A large body of empirical research has demonstrated the ubiquitous nature of the interactions that take place between vision and touch, with the former typically dominating over the latter. Many studies have investigated the influence of visual stimuli on the processing of tactile stimuli (and vice versa). Other studies, meanwhile, have investigated the effect of directing a participant’s gaze either toward or else away from the body-part receiving the target tactile stimulation. Other studies, by contrast, have compared performance in those conditions in which the participant’s eyes have been open versus closed. We start by reviewing the research that has been published to date demonstrating the influence of vision on the processing of tactile targets, that is, on those stimuli that have to be attended or responded to. We outline that many – but not all – of the visuotactile interactions that have been observed to date may be attributable to the direction of spatial attention. We then move on to focus on the crossmodal influence of vision, as well as of the direction of gaze, on the processing of tactile distractors. We highlight the results of those studies demonstrating the influence of vision, rather than gaze direction (i.e., the direction of overt spatial attention), on tactile distractor processing (e.g., tactile variants of the negative-priming or flanker task). The conclusion is that no matter how vision of a tactile distractor is engaged, the result would appear to be the same, namely that tactile distractors are processed more thoroughly.